STRATEGI PUBLIC RELATIONS PT. TELEKOMUNIKASI INDONESIA TBK DALAM MEMPERTAHANKAN REPUTASI PERUSAHAAN DAN MENCIPTAKAN EKOSISTEM DIGITAL YANG SEHAR SERTA INOVATIF MELALUI INDONESIA TELECOMMUNICATION AND DIGITAL RESEARCH INSTITUTE (ITDRI) - Felisitas Yolandita Suryo Kinasih; Agus Naryoso; Yanuar Luqman (Interaksi Online, 2023)
Designing a public relations strategy by a company is important in the process of achieving a company’s goals and ideals. This research aims to determine the process of PT. Telekomunikasi Indonesia Tbk carries out a public relations strategy to maintain reputation and create a healthy an innovative digital ecosystem through the Indonesia Telecommunication and Digital Research Institute (ITDRI). This research applies a descriptive case study method, a qualitative approach, and a constructivism paradigm. The techniques used are in-depth interview and pattern matching analysis techniques based on Institutional Theory, General Support Theory, 10 Steps Public Relations, and Relationship Management Theory. Pattern matching is carried out based on the company as a system, institutional formation, designing-implementation-evaluation strategy, and relationship management within the company. Analysis of the research results shows that there is an institutional process through ITDRI which is driven by community conditions and support from the government and the BUMN ministry. Through ITDRI, PT Telekomunikasi Indonesia designs and implements public relations strategies by implementing programs that can create a healthy and innovative digital ecosystem in Indonesia. This research states that companies and the community or surrounding environment have relationships that mutually influence each other and are often taken into consideration in decision making.